Pseudobartsia glandulosa, a new combination to replace Pseudobartsia yunnanensis (Orobanchaceae) - Yu, Wen-Bin; Li, De-Zhu; Wang, Hong (Phytotaxa, 2015)
Pseudobartsia Hong (1979: 406) was established during the preparation of the Chinese edition of Flora Republicae Popularis Sinicae. This genus only contains one species, Pseudobartsia yunnanensis Hong (1979: 406), which is endemic to Yunnan (Hong et al. 1998). Based on comparisons of type specimens, Tao (1993) found that Pseudobartsia yunnanensis can not be distinguished from Phtheirospermum glandulosum (Bentham 1846: 555) Hooker (1884: 304), which was originally only recorded from the Western Himalayas. Therefore, Pseudobartsia was treated as a synonym of Phtheirospermum Bunge ex Fischer & Meyer (1835: 35), and Pseudobartsia yunnanensis was regarded as a synonym of Phtheirospermum glandulosum in a full revision of Phtheirospermum by Tao (1996).